Przekształć wzory:
a) v=s:t wyznacz s
b) P=m*t t
c)E=mgh h
d) k=a:R R
e) y=0,25x x
f)K=1 : 4n n
g) y=2t - 1 t
h) v=at (do kwadratu) : 2 a
i) R=abc : 4P P
j) P=abx x
k)R=ax:b x
l) S=a:bx x
m) T=1:abx x
n) y=2t - 3x x
o) y=2(x-1) x
p) y=x-1:2 x
r) y=2: x-1 x
s) P=1/3 (a (do2) +2ax x



help!! ; ]

3

Odpowiedzi

2010-01-26T21:07:39+01:00
A) s= V*t
b) t= P:m
c) h=E:mg
d) R= a:k
e) x= 4y
f) n= 1:4K
g) t= (y+1):2
h) a= 2V:t^2
i) P= abc:4R
j) x= P:ab
k) x= Rb:a
l) x= a:bs
m) x= 1:abT
n) x= (2t-y):3
o) x= (y:2)+1
p) x= 2y+1
r) x= (2:y)+1
s) x= (3P-a^2):2a
Najlepsza Odpowiedź!
2010-01-26T21:10:10+01:00
A) V=s/t s=v*t
b) P=m*t t=P/m
c)E=mgh h=E/mg
d)k=a/R R=a/k
e) y=0,25x x=y/0,25
f)K=1/4n n=1/4K
g) y=2t - 1 t=(y+1)/2
h) v=at (do kwadratu) : 2 a= (2V)/t(do kwadratu)
i) R=abc /4P P=(abc)/4R
j) P=abx x=P/ab
k)R=ax/b x=Rb/a
l) S=a/bx x=a/Sb
m) T=1/abx x=1/Tab
n) y=2t - 3x x=(2t-y)/3
o) y=2(x-1) x=(y+2)/2
p) y=x-1/2 x=2y+1 (jesli to wyrazenie x-1 jest cale podzielone przez 2)
r) y=2/x-1 x=(2+y)/y
s) P=1/3 (a (do2) +2ax x=[3/2(P-1/3a(do kwadr.)]/a (jesli to wyrazenie sklada sie z jednej trzeciej * (a (do 2) +2ax)
2010-01-26T21:27:07+01:00
A) v=s:t //*t
s=vt
b) P=m*t //:m
t=P:m
c) E=mgh //:mg
h=E:mg
d) k=a:R //*R
a=kR //:k
R=a:k
e) y=0,25x //:0,25
x=y:0,25
f) K=1 : 4n //*4n
K4n=1 //:4K
n=1:4K
g) y=2t - 1 //+1
y+1= 2t //:2
t=(y+1):2
h) v=at (do kwadratu) : 2 //*2
2v=at (do kwadratu) //:t (do kwadratu)
a= 2v:t (do kwadratu)
i) R=abc : 4P //*4P
R4P=abc //:R4
P=abc:R4
j) P=abx //:ab
x=P:ab
k) R=ax:b //*b
Rb=ax //:a
x= Rb:a
l) S=a:bx //*bx
Sbx=a //:Sb
x=a:Sb
m) T=1:abx //*abx
Tabx=1 //:Tab
x=1:Tab
n) y=2t - 3x // -2t
y-2t=-3x //:-3
x= (-y+2t):3
o) y=2(x-1) //:2
y:2=x-1 //+1
x= (y:2)+1
p) y=x-1:2 //*2
2y=x-1 //+1
x=2y+1
r) y=2: x-1 //+1
y+1=2:x //*x
(y+1)x=2 //:y+1
x=2:y+1
s) P=1/3 (a (do2) +2ax //*3
3P= (a (do2) +2ax //:(a (do2)
3P:(a (do2)= 2ax //2a
x= (3P:(a (do2)):2a
1 5 1